The savvy caregiver [videorecording (DVD)] : a memory loss training program - Hepburn, Kenneth (HealthCare Interactive, 2007)
Introduces you to real-life family caregivers of those with memory loss and dementia, and gives specific ideas and strategies on how you can help your loved one.